The Antecedents of Loyalty Among Indonesian Airlines Passenger During Covid-19 Pandemic - Megawati Megawati; Vidyarini Dwita (Asian Journal of Management, Entrepreneurship and Social Science, 2022)
The purpose of this study is to investigate service quality and passenger satisfaction as the value of loyalty of passenger's style of acting in the comfort of passengers to fly to the destination safely during the COVID-19 epidemic. This study contributes to understanding the factors that influence passenger loyalty to airline services during the COVID-19 epidemic. The quantitative study was done among airline passengers who flew during the COVID 19 epidemic in 2020. A purposive sampling with non-probability sample was used to conduct an online survey for domestic aircraft passengers. The data reveal that service quality, satisfaction, and brand image all positively impact passenger loyalty, both directly and indirectly. Meanwhile, airline brand image has no moderating influence on service quality and passenger happiness to loyalty. There are numerous samples in the study and constraints in the conceptual framework. Furthermore, a comprehensive model can be utilized to investigate novel factors. Other variables, such as price, trust, or perceived values, may be included in future investigations.